Social, Economic, Demographic Factors and Proximate Determinants of Fertility in Papua Province - Syahmida S Arsyad; Darojad Nurjono Agung Nugroho; Arga Nugraha (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
The research on proximate determinants of fertility was carried out based on the condition of fertility in Papua which is still high compared to national figures and the use of modern contraception tends to decrease according to several periods of Indonesian Demographic and Health Surveys (IDHS). The purpose of this study is to examine the relationship between social, economic, demographic factors and the proximate determinant of fertility in Papua. This study is a secondary data the 2017 IDHS, analysis using descriptive and multivariate with multiple logistic regression test. The results show that Papuan women’s education has a dominant effect on the duration of marriage and the use of contraception. The higher education level will likely increase the use of contraception and the length of marriage. This can be used as a foothold in the planning and implementation of population control programs, in this case, is the regulation and restrictions on future births. Birth control programs through the Population, Family Planning, and Family Development Program need to synergize with other government programs, especially with the Education Program for Papuan women in planning, implementing, monitoring, and evaluating programs of course. An approach to traditional leaders is needed since customs and traditions greatly affect all aspects of Papuan people’s lives. The traditional leader’s advice and suggestions are very well heard by people. The traditional leader’s communication, information dissemination, and education to program targets really need to be strengthened. This method is certainly implemented by all levels of the program area, but especially in the field lines that are very close to the target.